Determine relation between serum levels of interleukin-6 and CRP with pulmonary involvement in progressive systemic sclerosis - Batool Zamani; Kamal Esalatmanesh; Ahmad Piroozmand; seyyed Alireza Moravveji; Elham Kolbedary (مجله علوم پزشکی فیض (پیوسته))
Background: Systemic sclerosis (SSc) is a connective tissue disorder characterized by excessive collagen deposition in skin and internal organs. Interstitial lung disease (ILD) is a late demonstration of SSc and cytokines can contribute to the disease pathology. This study aimed to determine relation between serum levels of interleukin-6 and CRP with pulmonary involvement in SSc. Materials and Methods: After obtaining consent, demographic data and serum levels of interleukin-6 were determined in 30 SSc with (case) and 30 without pulmonary involvement (control). Duration and activity status of disease, C-reactive protein (CRP), Chest x-ray and high resolution CT-scan (HRCT), ejection fraction (EF) and echocardiography findings and pulmonary artery pressure (PAP) were determined in two groups. Data analyzed with Mann-Whitney test, Chi-square test and Fisher’s exact test. Results: Mean age of case and control group ranged 52.5±9.3 and 43.9±9.7 years respectively (P=0.001). The serum levels of IL-6 in case and control groups were 73.1±95.4 and 46.7±83.6 pg/ml (P=0.267), respectively. IL-6 levels was significantly higher in male case compared to male control (P=0.007). Duration of SSc in case and control groups was 11.6±6.4 and 7.4±4.2 years (P=0.002). Also Quantitative CRP and PAP was significantly higher in case (P=0.01 and P<0.001, respectively). In the Case group 66.7% of them had reticulo-nodular pattern, whereas 28 (93.3%) of control had normal CXR (P<0.001). Conclusion: In SSc with pulmonary involvement serum, IL-6 levels is higher than without involvement but not statistically significant. Also, the CRP and PAP are benefit for evaluation of pulmonary involvement.